NHC-catalyzed enantioselective access to β-cyano carboxylic esters via in situ substrate alternation and release - Wang, Qingyun (2023)
A carbene-catalyzed asymmetric access to chiral β-cyano carboxylic esters is disclosed. The reaction proceeds between β,β-disubstituted enals and aromatic thiols involving enantioselective protonation of enal β-carbon. Two main factors contribute to the success of this reaction. One involves in situ ultrafast addition of the aromatic thiol substrates to the carbon-carbon double bond of the enal substrate. This reaction converts almost all enal substrate to a Thiol-click Intermediate, significantly reducing aromatic thiol substrates concentration and suppressing the homo-coupling reaction of enals. Another factor is an in situ release of enal substrate from the Thiol-click Intermediate for the desired reaction to proceed effectively. The optically enriched β-cyano carboxylic esters from our method can be readily transformed to medicines that include γ-aminobutyric acids derivatives such as Rolipram. In addition to synthetic utilities, our control of reaction outcomes via in situ substrate modulation and release can likely inspire future reaction development.